ANALISIS MANAJEMEN OPERASIONAL PERUSAHAAN MULTINASIONAL (Studi Kasus Pada PT. Unilever Indonesia Tbk.) - Sulthan Shaummil Faiq (JURNAL MANAJEMEN, 2021)
Operational management itself is a major management function in a company. This operations management has developed rapidly due to technological advances and the emergence of new innovations that have been implemented in business practices. Currently, many companies have looked at and made operations management a strategic tool for competing between companies. Operations management is needed to give birth to new innovations and changes for the better. Because along with the times, an increasingly advanced industry has also developed so that companies are required to present the best quality in products or services produced, but not forgetting the impact of the surrounding environment from all company activities.